2022
DOI: 10.13005/bpj/2540
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Profiling of Extract and Fractions of Bidara Upas (Merremia Mammosa (Lour.) Hallier F.) Tuber Using UPLCQToF-MS/MS

Abstract: Bidara upas (Merremia mammosa (Lour.) Hallier f.) tuber is empirically used to treat respiratory disorders and tuberculosis. The pharmacological effect is due to the activity of various secondary metabolites. This study aims to determine the metabolite profile of M. mammosa tuber ethanol extract, n-hexane fraction, ethyl acetate fraction, and n-butanol fraction. The dried powder of the tuber of M. mammosa was extracted with 96% ethanol. Then, liquid-liquid fractionation was performed using n-hexane, ethyl acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…The cytotoxic test with Vero E6 cells (host of the SARS-CoV2 virus) from the ethanol extract of bidara upas using the MTT method showed that the maximum non-toxic concentration (MNTC) is 500 µg/mL, as determined as the maximum concentration of the extract at which the cells developed normally, therefore the viral inhibition assay used 500 µg/mL as highest concentration [18,19]. The concentration that determined a cell viability above 80% [20]. However, in this research, the viability of cell is 41%.…”
Section: Resultsmentioning
confidence: 99%
“…The cytotoxic test with Vero E6 cells (host of the SARS-CoV2 virus) from the ethanol extract of bidara upas using the MTT method showed that the maximum non-toxic concentration (MNTC) is 500 µg/mL, as determined as the maximum concentration of the extract at which the cells developed normally, therefore the viral inhibition assay used 500 µg/mL as highest concentration [18,19]. The concentration that determined a cell viability above 80% [20]. However, in this research, the viability of cell is 41%.…”
Section: Resultsmentioning
confidence: 99%
“…Using Agilent LC-MS/MS QTOF, a total of 206 compounds were predicted from 96% of its ethanol extract, butanol fraction, ethyl acetate fraction, and nhexane fraction (Purwitasari, 2022). Through metabolite profiling were then subjected to a molecular docking study to predict the potential compounds that can inhibit the TMPRSS2 of SARS-CoV-2.…”
Section: Designmentioning
confidence: 99%
“…The objective of this research was to investigate the interaction between the spike protein of SARS-CoV2 and Merremia mammosa (Lour) through the process of docking. Previously, our investigation using LC-MS/MS QTOF equipment, discovered a total of 206 compounds in four different fractions (96% ethanol extract, butanol, ethyl acetate, and n-hexane) obtained from Merremia mammosa (Lour) (Purwitasari & Agil, 2022).…”
Section: Introductionmentioning
confidence: 99%